Implementasi Critical Path Method dalam Produksi Feature Radio â€œSudut Pandangâ€ Episode â€œMengenal Stuntingâ€ - Sulistyawati, Renjani Eka; Oktora, Dina Dwika (Jurnal Ilmiah Multimedia dan Komunikasi, 2022)
The production of radio feature â€œSudut Pandangâ€ Episode of â€œMengenal Stuntingâ€ imlements the Critical Path Method to map out all the steps need to be taken in order to complete and identify activities based on the priority; and also to identify the sequence of activities to complete first or need to be completed at the same time. It begins by determining the amount of time required to critically complete the priority work path, and analyzing the relationship between program requirements and available human resources, as well as the time required to complete production.The result of the Critical Path Method implementation is network analysis schedule that has succeeded in optimizing the total cost of production by reducing or accelerating the completion time of production activities in the creation of radio feature production works.